Fourier analysis with R - Valenzuela, Mississippi (2024)
Fourier analysis is currently one of the important parts of mathematical analysis. Fourier analysis methods are used in physics, electrical engineering, and other sciences to solve various problems. In this article we will give the main concepts of Fourier analysis and its applications in spectral analysis in solving problems using R, as shown in the examples.